The effect of ownership composition on earnings management: evidence for the Mexican stock exchange - San Martin Reyna, Juan Manuel (2018)
Purpose. This paper aims to examine the relationship between different types of shareholders that command share ownership, family, institutions or external blockholders and earnings management. In addition, it examines the effect of company size on earnings management. Design/methodology/approach. The sample includes 67 companies listed in the Mexican Stock Exchange for the period 2005-2015. The sample composition is quite industry-balanced. A cross-sectional version of the Jones model (1991) is to measure the earnings management. The GMM (generalized method of moments) model is also estimated. Findings. The results show that family and institutional ownership reduce the earnings management, but the impact is different depending on the company size. Research limitations/implications. The results show that there is a clear relationship between increasing participation of family and institutional investors and a reduction in earnings management. This is consistent with the literature that establishes that ownership is an effective regulatory mechanism that limits earnings management through closer supervision and involvement in management. Practical/implications. For companies’ corporate governance and regulatory authorities, the results of this study may serve to improve the decision-making. Originality/value. This study shows that ownership structure can provide corporate governance in Mexican listed companies with different monitoring and control capacities to influence companies’ strategies, particularly in relation to the discretion of earnings management. Doi: https://doi.org/10.1108/JEFAS-01-2017-0011